Hubungan asupan protein dan lemak dengan status kesehatan mulut anak usia prasekolah di Kecamatan Jetis Kabupaten Bantul D.I. Yogyakarta - Jatri Handijani; Al Supartinah; R Dwi Budiningsari (Jurnal Gizi Klinik Indonesia, 2006)
Background: The main problem of children’s oral cavity are caries and gingivitis. One cause of caries and gingivitis is plaque of which its formation and composition are affected by nutritional factor. Nutrition can be cariogenic or non-cariogenic both of which can bring direct or indirect impact to oral cavity. In the oral cavity both protein and fat are non-cariogenic.Objective: To identify the relationship between protein and fat intake with oral health status (level of caries seriousness, oral cleanliness, gingiva health and saliva acidity) of preschool children in Jetis subdistrict, Bantul District, Yogyakarta Special Territory.Methods: This was an observational study which used a cross sectional design. Subject of study were 100 children of 4-6 years old taken by using propotional random sampling. Data collected consisted of eating pattern, respondent characteristics, level of caries seriousness, oral cleanliness, gingiva health and saliva acidity. Data analysis used Person correlation statistic and linier regression. Data collected consisted of eating pattern, respondent characteristics, level of caries seriousness, oral cleanliness, gingival health status and saliva acidity. Data analysis used Pearson correlation statistic and linear regression tests.Results: Result of the study showed that there was relationship between protein and fat intake with oral cleanliness and saliva acidity (p<0.05) and there was no relationship between protein and fat intake with level of caries seriousness and gingiva health (p>0.05).Conclusion: There was relationship between protein and fat intake with oral health status (oral cleanliness and saliva acidity), but not with oral health status (level of caries serious- ness and gingiva health).